The Law Accountability of Tourists Who Violate "Tri Hita Karana" Principle in Balinese Cultural Tourism Maintenance - Herawati, Kadek Mery; Ni Ketut Supasti Dharmawan; Desak Putu Dewi Kasih; Anak Agung Istri Ari Atu Dewi (Formosa Journal of Science and Technology, 2024)
The disharmony between Laws and the Regulations of Balinese cultural tourism’s regulation and policy is still exist, specifically in terms of tourism management’s purpose and authority. The clarity of the purpose and the scope in the setting of Balinese cultural tourism Laws and Regulations need to be conducted comprehensively and structured, so the substantial dynamic that included and stated in the law will not be partial. According to the analysis of regulation content of laws and regulation for the application of Tri Hita Karana (THK) in Balinese culture tuorism’s operation, there are numerous disharmonisation that happened between Undang-undang Nomor 10 Tahun 2009 about tourism, as the Laws and Regulations that organizes the tourism, and sectoral Laws and Regulations that organizes limited tourism (whether forest, marine, and culture tourism). Although the disharmonisation already harmonized through Undang-undang Cipta Kerja (Laws of Work Creation), the comprehensive and structured clarity of purpose is still achieved yet, so the substantial dynamic that included and stated in the law will not be partial.